Determination of normative value of Psychometric hepatic encephalopathy score in Bangladeshi volunteers - Podder, Mrinmay Kumar; Aftab, Hafeza; Khalil, Md Musab; Hossain, Mohammad Iqbal; Hossain, Md Imran; Ullah, Parash; Fakruzzaman, Md (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background and Objectives: The psychometric hepatic encephalopathy score (PHES) is a composite score of five different neuropsychological tests. It is considered as gold standard test to diagnose Minimal Hepatic Encephalopathy(MHE). But one problem with PHES is that it needs normative value of its five components as they vary from population to population. So population based normative value should be derived before it is applied to that population. MHE is diagnosed when variation from this normal value occur, provided other criteria are fulfilled. The aim of this study is to find out the normative value of PHES test batteries. Methods: This cross sectional observational study among healthy volunteers took place in department of Gastroenterology, Dhaka medical college from May 2019 to April 2020. All participants in this study took part in the test according to international norm. Results: Among the 300 study population,age and years of education had significant impact on all tests score. Hence, multivariate equation adjusting age and years of education were derived. A scoring method was applied depending on deviation from predicted score for all tests. Finally, -5 PHES was determined as cut off value for normal and pathological. Conclusion: Age and education adjusted normative value of five components of PHES were constructed in Bangladeshi population. PHES cut off value was also determined. Now it is possible to calculate PHES among liver cirrhosis patients of Bangladesh. J Bangladesh Coll Phys Surg 2023; 41(4): 277-281